1997
DOI: 10.1242/jcs.110.6.687
|View full text |Cite
|
Sign up to set email alerts
|

The E-selectin-ligand ESL-1 is located in the Golgi as well as on microvilli on the cell surface

Abstract: Neutrophils and subsets of lymphocytes bind to E-selectin, a cytokine inducible adhesion molecule on endothelial cells. The E-selectin-ligand-1 (ESL-1) is a high affinity glycoprotein ligand which participates in the binding of mouse myeloid cells to E-selectin. The sequence of mouse ESL-1 is highly homologous to the cysteine rich FGF receptor (CFR) in chicken and the rat Golgi protein MG160. We have analysed the subcellular distribution of ESL-1 by indirect immunofluorescence, flow cytometry, various biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(7 citation statements)
references
References 37 publications
0
5
1
1
Order By: Relevance
“…The up-regulation of both membrane-bound and soluble E-selectin has been extensively documented (100 literature entries) in brain vascular system for its role in leukocyte rolling and recruitment in ischemic brain disease. In contrast, the up-regulation of E-selectin ligand-1, a major binding partner of E-selectin expressed by myeloid cells and not previously described in endothelial cells, was observed in both the cellular fraction of RBEC in vitro and in ischemic brain vessels in vivo . The functional role of this protein in inflammatory endothelial responses to ischemia remains unknown.…”
Section: Discussioncontrasting
confidence: 59%
“…The up-regulation of both membrane-bound and soluble E-selectin has been extensively documented (100 literature entries) in brain vascular system for its role in leukocyte rolling and recruitment in ischemic brain disease. In contrast, the up-regulation of E-selectin ligand-1, a major binding partner of E-selectin expressed by myeloid cells and not previously described in endothelial cells, was observed in both the cellular fraction of RBEC in vitro and in ischemic brain vessels in vivo . The functional role of this protein in inflammatory endothelial responses to ischemia remains unknown.…”
Section: Discussioncontrasting
confidence: 59%
“…The present study observed a change in the protein and mRNA expression of GLG1. The function of GLG1 and its different variants has been reported in several studies (35,(40)(41)(42)45,53,63,73). The aim of the present study was to report these phenomena.…”
Section: Discussionmentioning
confidence: 65%
“…In particular, GLG1 is a 160-kDa membrane sialoglycoprotein, originally isolated from the Golgi apparatus of rat neurons (32,33). Two homologs, the chicken cysteine-rich fibroblast growth factor receptor (CFR) (34) and ESL-1 (35)(36)(37), were identified in embryonic chick and murine myeloid cells, respectively. This FGF-binding protein has 16 cysteine-rich repeats in the extracellular luminal amino-terminal region, 21 amino acids in the transmembrane domain, and 13 amino acids in the intracellular cytoplasmic carboxy-terminal domain (Fig.…”
Section: Antitumor Effect Of Memantine Is Related To the Formation Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…(ICAM e VCAM) na superfície luminal dos vasos, que se ligam em seus receptores expressos constutivamente na membrana de neutrófilos (P-selectina ligante 1, Eselectina ligante 1 e L-selectina) promovendo o rolamento e o primeiro contato dos neutrófilos com as células endoteliais (Farsky e Mello, 1995;Farsky,Sannomiya e Garcia-Leme, 1995;Bruehl et al, 1997;Steegmaier et al, 1997;Buscher et al, 2010). Durante este contato inicial ocorre a ativação de vias de sinalização nos neutrófilos que regulam uma forte adesão entre as moléculas de adesão expressas nos neutrófilos (LFA-1 e Mac-1) e os seus ligantes (ICAM-1 e ICAM-2) expressos no endotélio ativado, diminuindo a velocidade de rolamento e permitindo a transmigração destas células até o foco inflamatório (Bunting et al, 2002).…”
Section: Neutrófilosunclassified